Influence of Cell-to-Cell Variations on the Inhomogeneity of Lithium-Ion Battery Modules. Issue 11 (1st January 2018) - Rumpf, Katharina; Rheinfeld, Alexander; Schindler, Markus; Keil, Jonas; Schua, Tobias; Jossen, Andreas
Abstract : Inhomogeneity within lithium-ion battery modules can occur due to variations in capacity and impedance of the connected cells as well as due to thermal gradients or cell connector design. We present a model for describing x S y P battery modules during operation, which is able to study these effects. The multidimensional multiphysics model includes a physicochemical model describing the electrochemical behavior of each cell. The electrical model accounts for the conservation of electric charge and energy between the cells to reach electrical consistency according to the respective module topology and cell interconnections. The model is capable of investigating the influence of defective and asymmetric cell connectors on the inhomogeneity of module operation. To evaluate this electrical influence, the observed inhomogeneities are compared to the influence of thermal gradients between the cells. The resulting inhomogeneous current distribution is presented for a module of two parallel connected lithium iron phosphate-graphite cells under constant current discharge operation for variations in cell capacity, cell impedance and ambient temperature at different module contact scenarios. From the observed impact of both, electrical and thermal variations between parallel connected cells, a matching strategy is derived and discussed which can enhance a module's performance during e.g. second life applications.